DITC control strategy for semi-direct drive system with switched reluctance motor in coal mine belt conveyor - LIU Peng; ZHANG Lei; BAO Jiusheng; CHEN Huaxin; WEI Chunji; MA Chuanming; WANG Lei; WANG Xiaolong (Gong-kuang zidonghua)
The underground belt conveyor at Pingdingshan Tian'an Coal Mining No. 9 Co., Ltd. uses a drive system consisting of an asynchronous motor, hydraulic coupling, and reduction gears. This system exhibits issues such as low transmission efficiency, lengthy transmission chain, and poor speed regulation performance. To address these limitations, the drive system was retrofitted with a 2×400 kW switched reluctance motor semi-direct drive(SRSD) system utilizing a switched reluctance motor(SRM) for the belt conveyor. A BP neural network was used to predict the flux linkage and torque of the SRM, and a highly accurate SRM nonlinear model was developed based on the predictions. By combining the torque variation patterns of the SRM in the commutation zone and the PWM control principles, an improved direct instantaneous torque control(DITC) strategy was proposed. Torque error was used as the input, and PWM control was applied to phase currents within the torque error threshold in this strategy. Simulations under no-load and variable load conditions of the belt conveyor were conducted. The results showed that the improved DITC strategy significantly reduced the torque ripple of SRM compared to the traditional DITC strategy, with a maximum reduction of 39.1%, thereby improving the operational stability of the SRSD system for the belt conveyor. Based on the key structural parameters of the SRM and the improved DITC strategy, the SRSD system for belt conveyors was developed and tested in an underground coal mine. The results showed that the SRSD system enabled smooth full-load startup, demonstrated excellent dynamic performance, and reduced power consumption by 24% compared to the original drive system.